The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1093/jnci/85.20.1644
|View full text |Cite
|
Sign up to set email alerts
|

Report of the International Workshop on Screening for Breast Cancer

Abstract: Randomized trials have provided stronger scientific evidence regarding the effectiveness of screening for breast cancer than for any other cancer. However, much still needs to be learned. Periodic gatherings of scientists in the field should speed the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
272
1
20

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 699 publications
(298 citation statements)
references
References 0 publications
5
272
1
20
Order By: Relevance
“…Rather, we believe that mammographic screening -proven to be sensitive in women at ages above 50 years (Nystrom et al, 1993) -provides the most plausible explanation (Fletcher et al, 1993) of the recent trends in Sweden. Population-based programmes were introduced in most counties of Sweden from 1987, with 20 of 26 counties included in 1989 and participation rates among invited women averaging 81% in the period 1993-95 (Olsson et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…Rather, we believe that mammographic screening -proven to be sensitive in women at ages above 50 years (Nystrom et al, 1993) -provides the most plausible explanation (Fletcher et al, 1993) of the recent trends in Sweden. Population-based programmes were introduced in most counties of Sweden from 1987, with 20 of 26 counties included in 1989 and participation rates among invited women averaging 81% in the period 1993-95 (Olsson et al, 1995).…”
Section: Discussionmentioning
confidence: 82%
“…2,3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results.…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…While the results of a number of randomized clinical trials have shown a clear reduction in breast cancer mortality with mammography screening in women over the age of 50 years, the benefit in younger women has been debated. 2,10 However the results of a recent meta-analysis of randomized clinical trials that included women in the 40 -49 years old age group showed significantly lower mortality rates in mammography screened women than in the control groups. 3 In spite of the reduced mortality, a study that evaluated the sensitivity of modern screening mammography by decade of age in a diverse population (36% nonwhite) showed that the sensitivity of mammography to detect invasive breast cancer was still lower among women aged 40-49 years compared with women aged 50 years or older (75% versus 92%).…”
Section: Adequacy Of Current Screening Guidelines For Young African Amentioning
confidence: 99%
“…especiall in youncer women (< 50 Xyears). still remains somew-hat controv-ersial (Fletcher et al 1993: Tabar et al 1995 In the present w-ork. we employed extensive clinical data from large mammogaraphv screening trials that should be representatiVe of the general population.…”
mentioning
confidence: 92%
“…especiall in youncer women (< 50 Xyears). still remains somew-hat controv-ersial (Fletcher et al 1993: Tabar et al 1995: see also Flehinger et al 1993 for lung cancer). As intersal cancer data indicate that not all prevalent tumours are detected by the screening procedure lHolmberg et al.…”
mentioning
confidence: 99%